Preparation of Retention of Manual to Electronic Medical Record Documents using Fishbone Diagram at Puskesmas Kauman Baru Ponorogo - Ananda Putri Nugroho; Rumpiati Rumpiati (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2024)
Retention preparation is the process of identifying, assessing, and grouping archives in accordance with the applicable retention schedule, before final action is taken on the archive. This study aims to determine the obstacles to retention preparation from manual to electronic at the Kauman Baru Ponorogo Health Center and the challenges of retention preparation. The research used descriptive qualitative method with data collection method. Data were obtained through observation of 33,445 medical record documents, as well as interviews with medical record officers. The research instrument included an observation sheet with five assessment components. The results showed that retention preparation still faced obstacles, especially in terms of facilities and infrastructure. One of the main obstacles is the limited storage space, which is narrow and not suitable to support the process of digitizing medical records. This study recommends increasing training, providing a new building that is suitable and safe for storage and the process of digitizing medical record documents can run effectively and in accordance with regulations.